The polymorphism rs3024505 proximal to IL-10 is associated with risk of ulcerative colitis and Crohns disease in a Danish case-control study - Tjønneland Anne; Jacobsen Bent A; Østergaard Mette; Christensen Jane; Ernst Anja; Andersen Vibeke; Krarup Henrik B; Vogel Ulla (BMC, 2010)
Abstract Background Crohns disease (CD) and ulcerative colitis (UC) are characterized by a dysregulated inflammatory response to normal constituents of the intestinal flora in the genetically predisposed host. Heme oxygenase-1 (HO-1/HMOX1) is a powerful anti-inflammatory and anti-oxidant enzyme, whereas the pro-inflammatory interleukin 1β (IL-1β/IL1B) and anti-inflammatory interleukin 10 (IL-10/IL10) are key modulators for the initiation and maintenance of inflammation. We investigated whether single nucleotide polymorphisms (SNPs) in the IL-1β, IL-10, and HO-1 genes, together with smoking, were associated with risk of CD and UC. Methods Allele frequencies of the IL-1β T-31C (rs1143627), and IL-10 rs3024505, G-1082A (rs1800896), C-819T (rs1800871), and C-592A (rs1800872) and HO-1 A-413T (rs2071746) SNPs were assessed using a case-control design in a Danish cohort of 336 CD and 498 UC patients and 779 healthy controls. Odds ratio (OR) and 95% confidence interval (95% CI) were estimated by logistic regression models. Results Carriers of rs3024505, a marker polymorphism flanking the IL-10 gene, were at increased risk of CD (OR = 1.40, 95% CI: 1.06-1.85, P = 0.02) and UC (OR = 1.43, 95% CI: 1.12-1.82, P = 0.004) and, furthermore, with risk of a diagnosis of CD and UC at young age (OR = 1.47, 95% CI: 1.10-1.96) and OR = 1.35, 95% CI: 1.04-1.76), respectively). No association was found between the IL-1β, IL-10 G-1082A, C-819T, C-592A, and HO-1 gene polymorphisms and CD or UC. No consistent interactions between smoking status and CD or UC genotypes were demonstrated. Conclusions The rs3024505 marker polymorphism flanking the IL-10 gene was significantly associated with risk of UC and CD, whereas no association was found between IL-1β or HO-1 gene polymorphisms and risk of CD and UC in this Danish study, suggesting that IL-10, but not IL-1β or HO-1, has a role in IBD etiology in this population.